El uso de la figura de Viriato en la pedagogía franquista (Estudios de Historia de España, 2016)
This article is about the use of the figure of Viriathus during the Franco dictatorial period. Occurs a true transfiguration of the lusitanian chief by assimilation to the dictatorial regime. It is important to know Franco pedagogy that has largely changed the lusitanian character. Likewise be known how has been evolving the figure of Viriathus during the dictatorship, offering a different image to your understanding in the democratic reality.
Keywords: Viriathus; Pedagogy; Franco Regime; School books; Archaelogy